Marginal seal evaluation of self-etch flowable composite materials - Janković Ognjenka; Radman Kuzmanović Irena; Adamović Tijana; Ilić Sanja; Đeri Aleksandra; Josipović Renata (Serbian Medical Society - Dental Section, Belgrade, 2013)
Introduction. The biggest drawback of composite materials is polymerization contraction and the existence of microcracks, therefore the market is now offering a wide variety of new composite materials. The aim of this study was to evaluate the marginal seal using dye method of class V cavities restored with self-etching flowable composite material Vertise Flow polymerized with different light-curing techniques. Material and Methods. The study was conducted on 60 extracted intact human teeth (30 premolars, 30 molars). Two cavities Class V (3×2×2 mm) were prepared in all teeth. Cavities on buccal surfaces were filled with self-etching flowable composite Vertise Flow (Kerr Dental Products), and on lingual with flowable composite Tetric Flow (Ivoclar Vivadent) using the corresponding adhesive systems. Polymerisation was performed using Bluephase Led flashlight C8 (Ivoclar Vivadent). Microleakage was tested using dye in a silver nitrate solution. Dye penetration was measured using stereo loupes with micrometer scale and six times magnification. Results. Linear dye penetration in intact molars restored using the classical polymerization technique and Vertise Flow composite was 3.41 μm while with Tetric Flow it was 4.23 μm. In intact molars restored using soft-start polymerization technique and Vertise Flow the dye penetration was 1.25 μm while for Tetric Flow it was 4.23 µm. Mean dye penetration in intact molars restored using pulse curing technique and material Vertise Flow was 1.02 μm while for the composite Tetric Flow it was 4.35 μm. In intact premolars restored using conventional curing technique and Vertise Flow dye penetration was 1.14 μm while for Tetric Flow it was 3.90 μm. Dye penetration in intact premolars restored using soft-start polymerization technique and Vertise Flow was 0.75 μm while for Tetric Flow it was 3.15 μm. Using a pulse polymerization technique and Vertise Flow in intact premolars dye penetration was 1.45 μm while for Tetric Flow it was 3.76 μm. Conclusion. Vertise Flow, self-etching flowable composite showed better marginal seal than flowable composite resin Tetric Flow. Smaller microcracks with Vertise Flow were confirmed after applying all three light-curing polymerization techniques.